Vitamin, Trace Element, and Fatty Acid Levels of Vitex agnus-castus L., Juniperus oxycedrus L., and Papaver somniferum L. Plant Seeds - Ozkaya, Ahmet; Ciftci, Harun; Yilmaz, Okkes; Tel, Ahmet Zafer; Cil, Erol; Cevrimli, B. Sitki (Hindawi Ltd, 2013)
The levels of fat-soluble vitamin, trace element and fatty acid of Vitex agnus-castus L., Juniperus oxycedrus L., and Papaver somniferum L. seeds in Turkey were determined by using HPLC, ICP-OES, and GC, respectively. In the Vitex agnus-castus L., Juniperus oxycedrus L., and Papaver somniferum L. seeds, linoleic acid (18 : 2) was determined with the highest level rates (%54.11, %28.03, and %72.14, resp.). In the Vitex agnus-castus L. seeds, R-tocopherol, alpha-tocopherol, and K-1 were determined as 9.70 mu g/g, 18.20 mu g/g, and 24.79 mu g/g, respectively; In the Juniperus oxycedrus L. seeds, R-tocopherol, alpha-tocopherol, and K-1 were determined as 18.50 mu g/g, 0.84 mu g/g, and 5.00 mu g/g, respectively, and in the Papaver somniferum L. seeds, R-tocopherol, alpha-tocopherol, K-1,K- and D-2 levels were determined as 43.25 mu g/g, 122.05 mu g/g, and 0.62 mu g/g, respectively. In the Vitex agnus-castus L., Juniperus oxycedrus L., and Papaver somniferum L. seeds, nickel (Ni), zinc (Zn), and iron (Fe) were determined with the trace element level rates (4.42 mg/kg, 10.43 mg/kg, 3.71 mg/kg for Ni, 7.00 mg/kg, 7.70 mg/kg, and 24 mg/kg for Zn and 93.73 mg/kg, 187.95 mg/kg, and 149.64 mg/kg for Fe, resp.). These parameters in seeds are very important for human life.
Keywords: Traditional Medicine; Chemical-Composition; Antioxidant Activity; Tocopherol Content; Folk Medicine; Oils; Phytosterol; Safflower; Turkey; Iron